Comparison of screening tests for gestational diabetes mellitus between "one step" and "two step" methods in an urban secondary care hospital – a prospective study - Ahire, Snehal S.; Mohanty, Swadhina B.; Bagaria, Shalini; Goswami-Giri, Prajakta (International Journal of Research in Medical Sciences, 2026)
Background: Gestational diabetes mellitus (GDM) is a common pregnancy complication linked to adverse maternal and fetal outcomes. Screening is crucial, but the optimal method remains debated. This prospective study aimed to compare the prevalence of GDM and associated pregnancy outcomes using the "one-step" (75 gm GTT, IADPSG criteria) versus the "two-step" (50 gm GCT followed by 100 gm OGTT, ACOG criteria) screening methods in an urban secondary care hospital setting in India. Methods: A total of 466 pregnant women (24-32 weeks gestation) were assigned to one-step (n=233) or two-step (n=233) GDM screening. Participants were followed until delivery for maternal and neonatal outcomes. GDM was diagnosed by established criteria for each method, and groups were compared. Results: Baseline characteristics were comparable. GDM prevalence was 9.4% (one-step) versus 5.2% (two-step), a non-statistically significant difference (p=0.075). No significant differences were found in maternal or neonatal outcomes (including treatments, complications, or birth outcomes) between screening groups, even among those diagnosed with GDM. Conclusion: In this setting, neither screening method demonstrated superior GDM detection rates or improved pregnancy outcomes. Larger, multicenter randomized controlled trials with cost-effectiveness analysis are recommended to determine the optimal GDM screening strategy for the Indian population.